Role of Radiotherapy in Metastatic Non-Small Cell Lung Cancer - Faria, Sergio L. (Frontiers in Oncology, 2014)
Radiotherapy has had important role in the palliation of NSCLC. Randomized trials tend to suggest that, in general, short regimens give similar palliation and toxicity compared to longer regimens. The benefit of combining chemotherapy to radiosensitize the palliative radiation treatment is an open question, but so far it has not been proved to be very useful in NSCLC. The addition of molecular targeted drugs to radiotherapy outside of approved regimens or clinical trials warrants careful consideration for every single case and probably should not be used as a routine management. Stereotactic radiosurgery (SRS) and stereotactic body radiation therapy (SBRT) are modern techniques being used each time more frequently in the treatment of single or oligometastases. In general, they offer good tumour control with little toxicity (with a more expensive cost) compared to the traditionally fractionated radiotherapy regimens.